Discovering nursing research - Flemming, Joyce; Fitch, Margaret (Operating Room Nurses Association of Canada Journal, 1990)
I discovered first hand that nursing research can be helpful to nurses in the operating room. Because of my recent experience I am convinced operating room nurses need to know about the research process and how it can help answer some of the questions they have about their practice.